Tonga : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1995)
This paper reviews economic developments in Tonga during 1990-95. During 1990/91-1991/92, GDP rose by an average of 3.4 percent, fueled by a fourfold increase in squash exports. In 1992/93, GDP growth quickened to 3.7 percent, largely on the basis of a rebound in construction and a rise in domestically oriented manufacturing production-and despite a sharp fall in squash exports. In 1993/94, growth reached 4.7 percent, as squash exports again increased, construction boomed, and commerce accelerated.